-3b+5b=2(2-b)+6(b-2)

Simple and best practice solution for -3b+5b=2(2-b)+6(b-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3b+5b=2(2-b)+6(b-2) equation:


-3b+5b=2(2-b)+6(b-2)

We simplify the equation to the form, which is simple to understand
-3b+5b=2(2-b)+6(b-2)

Reorder the terms in parentheses
-3b+5b=+(+4-2b)+6*(b-2)

Remove unnecessary parentheses
-3b+5b=+4-2b+6+*(+b-2+)

Reorder the terms in parentheses
-3b+5b=+4-2b+(+6b-12)

Remove unnecessary parentheses
-3b+5b=+4-2b+6b-12

We move all terms containing b to the left and all other terms to the right.
-3b+5b+2b-6b=+4-12

We simplify left and right side of the equation.
-2b=-8

We divide both sides of the equation by -2 to get b.
b=4

See similar equations:

| 4w+8=88 | | +2=7 | | (9x^4-6x^2+1)-(x^4-12x^3+34x^2+12x+1)=0 | | 2660+x(175.75)=5999.25 | | 72-x=86-2x | | -9+-5+14+-6= | | 5q+8=11 | | 2(3x+4y)=4x+2y | | 180-36-x=102 | | (13x-1)= | | 6+-4+-9+7= | | 0-8b=12 | | 4w+5z=6 | | 10x-1=1-4x | | 6y=5x+3 | | 3b+5b=2(2-b)+6(b-2) | | 3x-24=2x+35 | | 1.4x-0.9=33 | | (10x+29)= | | 5(y+4)=-8y-45 | | 6+2=14-x | | 315+15p=450 | | 8x-6-3x=4 | | -x+3y-4z=-15 | | 200p+40p=350+50p | | 14=n+2 | | 6-4t=10 | | 180=4y+(x+2y) | | x=-2y+5z-9 | | t^2+4t-1=t^2+2t+2 | | -2x^2+8x-9=0 | | 2(2k^2+81)-k= |

Equations solver categories